2015
DOI: 10.1523/jneurosci.0440-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptors in the Central Nucleus of the Amygdala Mediate Cisplatin-Induced Malaise and Energy Balance Dysregulation through Direct Hindbrain Projections

Abstract: Cisplatin chemotherapy is used commonly to treat a variety of cancers despite severe side effects such as nausea, vomiting, and anorexia that compromise quality of life and limit treatment adherence. The neural mechanisms mediating these side effects remain elusive despite decades of clinical use. Recent data highlight the dorsal vagal complex (DVC), lateral parabrachial nucleus (lPBN), and central nucleus of the amygdala (CeA) as potential sites of action in mediating the side effects of cisplatin. Here, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…The current study investigated the neurochemical phenotype and functional significance of hindbrain-forebrain neuronal populations mediating cisplatin-induced anorexia and weight loss in an experimental rat model. Building upon previous findings suggesting that glutamate receptor signaling from CeA-projecting lPBN CGRP neurons triggers anorexia (Carter et al, 2013;Alhadeff et al, 2015), we demonstrate that lPBN¡CeA neurons expressing CGRP are glutamatergic and play a role in mediating cisplatin-induced anorexia. Chemogenetic inhibition of this excitatory projection attenuated cisplatin-induced anorexia and Table of Pearson's and Mander's correlation coefficients for colocalization of CGRP and VGLUT2.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The current study investigated the neurochemical phenotype and functional significance of hindbrain-forebrain neuronal populations mediating cisplatin-induced anorexia and weight loss in an experimental rat model. Building upon previous findings suggesting that glutamate receptor signaling from CeA-projecting lPBN CGRP neurons triggers anorexia (Carter et al, 2013;Alhadeff et al, 2015), we demonstrate that lPBN¡CeA neurons expressing CGRP are glutamatergic and play a role in mediating cisplatin-induced anorexia. Chemogenetic inhibition of this excitatory projection attenuated cisplatin-induced anorexia and Table of Pearson's and Mander's correlation coefficients for colocalization of CGRP and VGLUT2.…”
Section: Discussionsupporting
confidence: 79%
“…We reported recently that cisplatin activates lPBN CGRP neurons that project to the CeA and that glutamate receptor signaling within the CeA is required for cisplatininduced malaise and energy balance dysregulation (Alhadeff et al, 2015). It has been suggested that glutamate signaling mediates the anorexia resulting from activation of CGRP neurons within the lPBN (Carter et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations